2021
DOI: 10.1108/wje-02-2021-0094
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and durability properties of adobe blocks filled with date palm wastes

Abstract: Purpose Earthen construction does not meet today’s requirements due to certain limitations such as low water resistance and its high vulnerability to cracking damage. The purpose of this study is to improve the mechanical properties and low durability of adobe blocks by incorporating date palm wastes as a natural reinforcement and lime as a stabilizer. Design/methodology/approach Soil from the region of Biskra in Algeria was mixed with sand and lime in suitable ratios. Then, date palm wastes were added to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…However, it was noticed that the weight loss decreases as the date palm waste is added during each wetting/drying cycle. These findings are similar to those found in the study conducted by Zaidi et al [31]. It was indeed revealed that, after twelve wetting/drying cycles, the weight losses for bricks cured with the MS curing mode decreased from 5.8% to 4.3%, while for those cured with the AF curing mode, these weight losses dropped from 9.1% to 7.2%.…”
Section: Total Absorptionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, it was noticed that the weight loss decreases as the date palm waste is added during each wetting/drying cycle. These findings are similar to those found in the study conducted by Zaidi et al [31]. It was indeed revealed that, after twelve wetting/drying cycles, the weight losses for bricks cured with the MS curing mode decreased from 5.8% to 4.3%, while for those cured with the AF curing mode, these weight losses dropped from 9.1% to 7.2%.…”
Section: Total Absorptionsupporting
confidence: 91%
“…These researchers have in fact demonstrated that DPWs have a strong hydrophilicity; they also showed that these fibers can absorb water up to four times their dry weight. Comparable findings have been reported in investigation curried out by other studies [29,31]. It should be noted that the standard established by Walker [46] recommends that the total absorption capacity should not exceed 20%.…”
Section: Total Absorptionsupporting
confidence: 78%
See 2 more Smart Citations
“…The ease of modification and portability of the program enhances the user convenience [7][8]. The application of Simulink to build control models is easy to learn, has a clear structure, high control accuracy and compilation efficiency, and fits closely with actual experiments, so it is widely used in signal control, analysis, and processing [ [9].…”
Section: Software Introductionmentioning
confidence: 99%